Right/Left Ventricular Blood Pool T2 Ratio as an Innovative Cardiac MRI Screening Tool for the Identification of Left‐to‐Right Shunts in Patients With Right Ventricular Disease. Issue 5 (10th August 2021) - Emrich, Tilman; Bordonaro, Veronica; Schoepf, U. Joseph; Petrescu, Aniela; Young, Gabrielle; Halfmann, Moritz; Schoeler, Theresia; Decker, Josua; Abidoye, Ibukun; Emrich, Anna Lena; Kreitner, Karl‐Friedrich; Schmidt, Kai Helge; et al.
Abstract : Background: Left‐to‐right (L‐R) shunts are characterized by a pathological connection between high‐ and low‐pressure systems, leading to a mixing of oxygen‐rich blood with low oxygenated blood. They are typically diagnosed by phase‐contrast cardiac magnetic resonance imaging (MRI) which requires extensive planning. T2 is sensitive to blood oxygenation and may be able to detect oxygenation differences between the left (LV) and right ventricles (RV) caused by L‐R shunts. Purpose: To test the feasibility of routine T2 mapping to detect L‐R shunts. Study Type: Retrospective. Population: Patients with known L‐R shunts ( N  = 27), patients with RV disease without L‐R shunts ( N  = 21), and healthy volunteers (HV; N  = 52). Field Strength/Sequence: 1.5 and 3 T/balanced steady‐state free‐precession (bSSFP) sequence (cine imaging), T2‐prepared bSSFP sequence (T2 mapping), and velocity sensitized gradient echo sequence (phase‐contrast MRI). Assessment: Aortic (Qs) and pulmonary (Qp) flow was measured by phase‐contrast imaging, and the Qp/Qs ratio was calculated as a measure of shunt severity. T2 maps were used to measure T2 in the RV and LV and the RV/LV T2 ratio was calculated. Cine imaging was used to calculate RV end‐diastolic volume index (RV‐EDVi). Statistical Tests: Wilcoxon test, paired t ‐tests, Spearmen correlation coefficient, receiver operating curve (ROC) analysis. Significance level P  < 0.05. Results: The Qp/Qs and T2 ratios in L‐R shunt patients (1.84 ± 0.84 and 0.89 ± 0.07) were significantly higher compared to those in patients with RV disease (1.01 ± 0.03 and 0.72 ± 0.10) and in HV (1.04 ± 0.04 and 0.71 ± 0.09). A T2 ratio of >0.78 showed a sensitivity, specificity, and negative predictive value of 100%, 73.9%, and 100%, respectively, for the detection of L‐R shunts. The T2 ratio was strongly correlated with the severity of the shunt ( r  = 0.83). Data Conclusion: RV/LV T2 ratio is an imaging biomarker that may be able to detect or rule‐out L‐R shunts. Such a diagnostic tool may prevent unnecessary phase‐contrast acquisitions in cases with RV dilatation of unknown etiology. Level of Evidence: 3 Technical Efficacy: Stage 2